Agreement for the management of the Brac University cafeteria and catering services along with kitchen operation - Brac University (Brac University, 2023)
This agreement made between Brac University and Khabar Dabar Catering for the management of the Brac University cafeteria and catering services along with kitchen operation for the Brac University new campus project.